2020
DOI: 10.3390/ijms21082779
|View full text |Cite
|
Sign up to set email alerts
|

“Mitotic Slippage” and Extranuclear DNA in Cancer Chemoresistance: A Focus on Telomeres

Abstract: Mitotic slippage (MS), the incomplete mitosis that results in a doubled genome in interphase, is a typical response of TP53-mutant tumors resistant to genotoxic therapy. These polyploidized cells display premature senescence and sort the damaged DNA into the cytoplasm. In this study, we explored MS in the MDA-MB-231 cell line treated with doxorubicin (DOX). We found selective release into the cytoplasm of telomere fragments enriched in telomerase reverse transcriptase (hTERT), telomere capping protein TRF2, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
93
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(105 citation statements)
references
References 108 publications
(144 reference statements)
10
93
0
2
Order By: Relevance
“…Although currently the study of IM in human cancer is in infancy [62], the IM related to telomere DSBs well fits several peculiarities found in tumors: cellular senescence linked to telomere attrition, polyploidy associated with cellular senescence, mitotic slippage, reprogramming, and alternative telomere lengthening characteristic for some cancers [62]. We proposed a hypothesis that ALT-associated PML bodies in mitotic slippage of tumor cells may serve as a site for IM recombination repair [177]. Interestingly, the meiotic genes involved in the homology search and recombination RAD21L (Rec8 paralog) and Hop2-Mnd1 heterodimer (RAD51-dependent) were found associated with ALT [178,179].…”
Section: Brainstorming Sessionmentioning
confidence: 53%
See 2 more Smart Citations
“…Although currently the study of IM in human cancer is in infancy [62], the IM related to telomere DSBs well fits several peculiarities found in tumors: cellular senescence linked to telomere attrition, polyploidy associated with cellular senescence, mitotic slippage, reprogramming, and alternative telomere lengthening characteristic for some cancers [62]. We proposed a hypothesis that ALT-associated PML bodies in mitotic slippage of tumor cells may serve as a site for IM recombination repair [177]. Interestingly, the meiotic genes involved in the homology search and recombination RAD21L (Rec8 paralog) and Hop2-Mnd1 heterodimer (RAD51-dependent) were found associated with ALT [178,179].…”
Section: Brainstorming Sessionmentioning
confidence: 53%
“…While the majority of somatic cells are deficient in active telomerase, cancer cells not only can reactivate telomerase, but can also initiate a mechanism of the alternative telomere maintenance (ALT) in the absence of telomerase activity [176] or undergo transient ALT [177]. Some meiosis genes were found associated with supposed homology search in ALT [178,179].…”
Section: Melanoma and Meiosis Specific Ct (Meict) Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous studies, by using an immunostaining method, we showed that giant cells, which originate due to the mitotic slippage, eventually acquired an amoeboid phenotype and bud the depolyploidized progeny, restarting the mitotic cycling [29]. Here, we show some more pictures which illustrate aberrant mitosis and cell budding (Figure 4a We extended our studies by using live cell imaging, employing two different methodsholographic microscopy (HoloMonitor4, LabSoft, Warsaw, Poland) and scanning disc confocal microscopy (Zeiss, Oberkochen, Germany).…”
Section: Atypical Divisions Of Polyploid/senescent Cellsmentioning
confidence: 99%
“…issue [29] ( Figure S1a). Namely, we treated cells for one day (D1) with 100 nM doxorubicin (dox), which yielded the highest number of SA-β-gal-positive cells without a cytotoxic effect.…”
Section: Doxorubicin-induced Senescence Of Mda-mb-231 Cellsmentioning
confidence: 99%